Penerapan Manajemen Dan Produksi Yang Baik Untuk meningkatkan Pendapatan usaha Kecil Kerupuk Di Kuin Utara Banjarmasin - Ali Sadikin; Fahmi Roy Dalimunthe; Nadia Zulfati Fairuz; Dina Nugraheni (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2023)
Various problems of small micro, small and medium enterprises (UMKM) in Indonesia, one of which is that they have not applied good business management and production aspects to the businesses they run. From the survey we conducted at the RUSLIANI cracker business in Jl Kuin Utara Alalak Banjarmasin, both the management and production aspects still do not apply good business management. One of the problems in the business management aspect is the marketing that they have been doing in the Rusliani crackers business, which only does local marketing (traditional methods) such as selling in front of her house or around her neighborhood. Mrs. Rusliani's sales and opinions continue to fall, especially in the last 2 years during the Covid-19 pandemic where sales turnover is only around IDR 750,000 - IDR 900,000 per month. In the production aspect of this Kerupuk-RUSLIANI business, from the past it has only produced haruan crackers, not yet diversified products and very traditional cracker packing. The target of this service is that with literacy about good management and production in the business, it is hoped that the Kerupuk-RUSLIANI business with e-marketing such as Instagram, whatsupp business etc. and adding product variants (diversification) to other processed cork fish such as shredded Haruan, haruan skin etc., now sales have increased and Mrs. Rusliani's income has increased to Rp 1,200,000- Rp 1,500,000 per month.